Recent Advances in Organocatalytic Cascade Reactions toward the Formation of Quaternary Stereocenters - Vetica, Fabrizio; de Figueiredo, Renata Marcia; Orsini, Monica; Tofani, Daniela; Gasperi, Tecla (Synthesis, 2015)
This review provides the authors’ selection of recent publications that highlight the increasing efforts to develop valuable organocatalytic domino/tandem/cascade reactions as the main tool in the creation of quaternary stereocenters.1 Introduction2 Diarylprolinol Ethers and Proline Derivatives3 Imidazolidinones4 Brønsted Acids5 Cinchona Alkaloids6 Thioureas7 Squaramides8 N-Heterocyclic Carbenes9 Outlook and Conclusions
Keywords: domino reaction; tandem reaction; quaternary stereocenter; asymmetric catalysis; organocatalysis